Correlation between parameters of volumetric capnography and spirometry during a submaximal exercise protocol on a treadmill in patients with cystic fibrosis and healthy controls - Parazzi P.L.F. (2019)
© 2018 Sociedade Portuguesa de Pneumologia Introduction: Spirometry is the most frequently used test to evaluate the progression of lung damage in cystic fibrosis (CF). However, there has been low sensitivity in detecting early lung changes. In this context, our objective was to identify the correlation between parameters of volumetric capnography (VCap) and spirometric parameters during a submaximal treadmill exercise test. Methods: A cross-sectional and controlled study which included 64 patients with CF (CFG) and 64 healthy control subjects (CG) was performed. The CFG was from a university hospital and the CG from local schools. All participants underwent spirometry and VCap before, during and after the submaximal treadmill exercise test. The main variable analyzed by VCap was the slope of phase 3 (slope 3), which indicates the [exhaled carbon dioxide] at the end of expiration, and expresses the heterogeneity of gas emptying in pulmonary periphery. The correlation analysis between spirometry and VCap was conducted using the Spearman correlation test, considering α = 0.05. Results: The indices analyzed by VCap showed correlation with parameters of VCap. Slope 3 showed an inverse correlation with forced expiratory volume in the first second of forced vital capacity (FEV 1 ) in both groups and at all moments of the submaximal treadmill exercise test. Forced vital capacity (FVC) and FEV 1 /FVC ratio showed an inverse correlation with slope 3 only for CFG. Values of slope 3 corrected by the spontaneous tidal volume (VT) and end-tidal carbon dioxide tension (PetCO 2 ) showed results similar to slope 3 analyzed separately. Conclusion: Parameters of VCap such as slope 3, slope 3/VT and slope 3/PetCO 2 correlated with sensitive variables of spirometry such as FEV 1 , FVC and FEV 1 /FVC ratio. For the evaluated variables, there was consistency in the correlation between the two tests, which may indicate the impact of CF on pulmonary physiology.